Effect of Micropolar Fluid to Study the Characteristics of Squeeze Film Between Porous Curved Annular Plates - Chaithra, N.; Hanumagowda, B. N. (Communications in Mathematics and Applications, 2023)
This study examines the effect of micropolar fluid lubricants on porous curved annular plates through a squeeze film lubrication approach. Squeeze film characteristics have been determined using a modified version of the Reynolds equation. Micropolar fluid has an improved impact on the squeeze film pressure, load bearing capacity, and squeeze film time compared to the Newtonian case, whereas porosity has an adverse effect on squeeze film characteristics.